A novel piezoelectric ceramic with high Curie temperature and high piezoelectric coefficient. Issue 5 (1st April 2020) - Huang, Siyu; Zeng, Jiangtao; Zheng, Liaoying; Man, Zhenyong; Ruan, Xuezheng; Shi, Xue; Li, Guorong
Abstract: 0.02Pb(Sb1/2 Nb1/2 )O3 -0.98Pb1-x Bax (Zr0.53 Ti0.47 )O3 (PSN-PBx ZT) ceramics with high Curie temperature and high piezoelectric properties were prepared by traditional solid state reaction measurement to meet the requirements for high temperature applications, and the crystal structure, dielectric, piezoelectric and ferroelectric properties were investigated. All the samples show a tetragonal crystal structure at room temperature and there was no noticeable change with the increasing of Ba 2+ content. Doping of Ba 2+ markedly improved piezoelectric properties of PSN-PZT, the maximum d33 560 pC/N, Tc 317 °C at x = 0.05. Their outstanding piezoelectric properties will drive the development of high temperature industrial applications.